A СHOICE IN THE RELATIONSHIPS OF EXCHANGE - V. Kuligin (Вестник университета)
In a condition of division of labor a voluntary exchange lead to a common good. Motive forces of exchange are been the economic interests. A collaboration of individuals is examined as a result of the conscious choice. A fact itself of the choice is interpreted as a subjective process of valuation of a good. All economic innovations go through a procedure so of valuation. However being at the same time uncertainty is inestimable. A common good is eventually been unintended and unforeseen sequel for the market agents.